POLA ALOKASI WAKTU DAN KONTRIBUSI PENDAPATAN PEREMPUAN PEDAGANG SAYURAN DI PASAR PINASUNGKULAN KAROMBASAN MANADO - Angelina ., Pesik; Jenny ., Baroleh; Rine ., Kaunang (Sam Ratulangi University, 2016)
This study aims to determine the pattern of time allocation of women vegetable traders and their contribution to the household income. This research was conducted in Pinasungkulan Market, Karombasan, Manado for two month from June to July 2016. The primary data was collected from interviews with 15 women vegetable sellers who have a family. Secondary data were obtained from Sub-office Pinasungkulan Market. Data analysis was used descriptive analysis techniques. The results showed that, in general, women vegetables traders in the Pinasungkulan Market have started selling vegetables after they were married. Because as wives, they realized that they have to support their husbands to earn money for a living because of their husband's income is not sufficient. Time allocation patterns of the woman vegetable seller shave used an average of 15 hours per day for all their activities. They are selling vegetables, domestic activities and others social activities. Their time allocation daily respectivley consists of sold vegetables activities spend on average 8.9 hours (59.40%), for households 2, 6 hours/day (17.30%) and for other activities such as watching television and attending worship and other social activities, an average of 3.5 hours (23.3%). The conclusion from this study that the pattern of time allocation by women vegetable vendors in the Market of Pinasungkulan, Karombasan, women spend more time on economic activities than from domestic activities. Women vegetable sellers have earned average income of IDR 4.400 million per month with a 59.27% ​​contribution to the family income. While their husband shave contributed to the family income is lower than the wife of 19.09% with an average income of IDR 1.417 million per month. The contribution of other members of the household is income, especially children, are IDR 1.607 million per month (21.64%). Therefore, it can be concluded that women vegetables traders in Pinasungkulan Market are primary source of support for family.